Study of retirees and their leisure activities in a public space. - Shen, Weixiong (2015)
In a society characterized by rapid ageing and increased life expectancy, we will witness a profound age shift in our demographic history. The proportions of seniors are expected to rise from 8.4% in 2005 to 18.7% in 2030. As a result, older persons in Singapore will experience retirement quite differently from earlier generations. Presenting an ethnographic study of a public space in Singapore, this paper will examine (a) the nature of leisure activities of the retirees in a public space, (b) the roles these activities play in their personal and social needs, and (c) the strategies they adopt in order to stay relevant in a fast-paced society. The ethnographic study reveals that participating in leisure activities and having extra-familial social support can induce a positive lifestyle and enhance life satisfaction among the retirees. The study also suggests the need for policy makers to consider the seniors’ needs when designing public amenities in Singapore.